Promiscuous, diseased and unfit: Discourses and embodiments of Indian indentured women across the British Empire, c. 1840–1920 - Morag Flora Wright (Journal of Indentureship and its Legacies)
Indian women represented something of a persistent problem for colonial officials. The Indian Government consistently emphasized the importance of obtaining high numbers of indentured women, as the lack of women on plantations was portrayed as leading to so-called vice and ‘immoral’ sexual relations. For the plantation colonies, women represented the social reproduction of the workforce, through their domestic and reproductive labour. I chart three imperial discourses which attempted to embody indentured women in markedly different ways: as promiscuous wives, as diseased and as possessors of unfit wombs. Through these embodiments I explore how the increasing violences and failures of the indenture system interacted with nineteenth-century understandings of race to map these problems not onto the system of indenture but onto the bodies of indentured women. I look at how a particularly medicalized language around women created by colonial officials sought to control, border and embody the concept of the woman worker as inherently racially deficient. In doing so the colonial states involved in indentured labour positioned themselves as father, as correctors of racial deviancy and indenture as a system, by extension, as a means of stepping into subjecthood, history and civility.